Social injustice and public health - Levy, Barry S.; Sidel, Victor W. (New York ; Oxford : Oxford University Press, 2006)
This text defines social injustice as the active denial or violation based on the perception of the inferiority of specific groups. These groups are socially defined in terms of racial or ethnic status, language, country of origin, gender, sexual orientation or other perceived group characteristic.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Social medicine; Social justice; Public health -- Social aspects